PEDAGOGICAL AND PSYCHOLOGICAL FOUNDATIONS OF THE STEAM EDUCATION SYSTEM. (Universal International Scientific Journal, 2026)
This article describes the interdisciplinary relationship of "Natural Sciences" in primary education based on the STEAM approach. That is, it describes how "Natural Sciences" interact with other subjects in an integrative process and how interdisciplinary relationships are highlighted based on the STEAM approach. For the first time in our country, STEAM education is being introduced in primary schools in general education, teaching "Natural Sciences". The theories that any approach presents to the field of education are also highlighted.
Keywords: technology, natural sciences, integration, interdisciplinary connection.